Macrozoobenthos as a Bioindicator of Pollution in the Malaka Strait Waters, Indonesia - Djunaidi Djunaidi; Perdana Putra Kelana; Tyas Dita Pramesthy; Muhammad Nur Arkham; Rangga Bayu Kusuma Haris (Institut Pertanian Bogor, 2025)
Macrozoobentos are known as organisms that are sensitive to environmental changes, so they are widely used as biological indicators of a water. This study aims to determine the types of macrozoobenthos, the level of diversity, uniformity, and dominance of macrozoobenthos, including the family biotic index (FBI) to detect water quality in Dumai City. The method used was a survey with stations determined through the purposive sampling. Macrozoobenthos samples were collected using a line transect with a square transect and a core sampler. A total of 381 macrozoobentos individuals found in the waters of Dumai City consisted of 6 species from the Gastropods class (Nerita articulata, Chicoreus capucinus, Littorina scabra, Ellobium aurisjudae, Cerithidae quoyii, and Pugilina cochlidium); Bivalvia class: 1 family and 1 species (Polymesoda bengalensis). The highest macrozoobenthos density was found at Station 3 (125 ind/m2) and the lowest at station 1 (21 ind/m2). The Shannon-Wienner diversity index ranged between 1.17 and 1.52. The diversity index at all stations was relatively low, the macrozoobenthos uniformity index was high (0.654697-to 0.783512), and the dominance index was relatively low (0.234078-to 0.43574). The Shannon-Wienner Index and the dominance index are also relatively low. Further testing using the FBI showed differences in water quality: Station 1 was adequate, Station 2 was poor, while Station 3 was somewhat poor. Monitoring macrozoobenthos diversity can be helpful in detecting changes or disturbances in ecosystems. Keywords: bioindicator, diversity, Family Biotik Index, macrozoobenthos